2013
DOI: 10.1186/1471-2091-14-33
|View full text |Cite
|
Sign up to set email alerts
|

AGG/CCT interruptions affect nucleosome formation and positioning of healthy-length CGG/CCG triplet repeats

Abstract: BackgroundFragile X Syndrome (FXS), the most common inherited form of mental retardation, is caused by expansion of a CGG/CCG repeat tract in the 5′-untranslated region of the fragile X mental retardation (FMR1) gene, which changes the functional organization of the gene from euchromatin to heterochromatin. Interestingly, healthy-length repeat tracts possess AGG/CCT interruptions every 9–10 repeats, and clinical data shows that loss of these interruptions is linked to expansion of the repeat tract to disease-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…It has been noticed that the number of repeats, the content of interspersed AGG and the haplotype are able to influence the stability of FMR1 (Oberlé et al, 1991 ; Eichler et al, 1994 ; Gunter et al, 1998 ; Hirst and White, 1998 ; Taylor et al, 1999 ; Larsen et al, 2000 ; Dombrowski et al, 2002 ; Nolin et al, 2003 , 2013 , 2015 ; Yrigollen et al, 2012 , 2013 , 2014 ; Avitzour et al, 2014 ; Weiss et al, 2014 ). AGG interruptions, for instance, have been indicated to support the stability of FMR1 by reducing secondary structure formation (Weisman-Shomer et al, 2000 ; Jarem et al, 2010 ) and promoting appropriate DNA conformations (Jarem et al, 2010 ) as well as adequate DNA packing (Mulvihill et al, 2005 ; Volle and Delaney, 2013 ). Furthermore, the number of repeats was shown to directly correlate with the instability of the tandem tracts (Oberlé et al, 1991 ; Eichler et al, 1994 ; Taylor et al, 1999 ; Avitzour et al, 2014 ): it is assumed that the size of G-rich tracts directly correlates with the formation of secondary structures and polymerase slippage during replication (Mornet et al, 1996 ; Freudenreich et al, 1997 ; Weitzmann et al, 1997 ; Hirst and White, 1998 ).…”
Section: The Fragile X Syndrome — Of Menmentioning
confidence: 99%
“…It has been noticed that the number of repeats, the content of interspersed AGG and the haplotype are able to influence the stability of FMR1 (Oberlé et al, 1991 ; Eichler et al, 1994 ; Gunter et al, 1998 ; Hirst and White, 1998 ; Taylor et al, 1999 ; Larsen et al, 2000 ; Dombrowski et al, 2002 ; Nolin et al, 2003 , 2013 , 2015 ; Yrigollen et al, 2012 , 2013 , 2014 ; Avitzour et al, 2014 ; Weiss et al, 2014 ). AGG interruptions, for instance, have been indicated to support the stability of FMR1 by reducing secondary structure formation (Weisman-Shomer et al, 2000 ; Jarem et al, 2010 ) and promoting appropriate DNA conformations (Jarem et al, 2010 ) as well as adequate DNA packing (Mulvihill et al, 2005 ; Volle and Delaney, 2013 ). Furthermore, the number of repeats was shown to directly correlate with the instability of the tandem tracts (Oberlé et al, 1991 ; Eichler et al, 1994 ; Taylor et al, 1999 ; Avitzour et al, 2014 ): it is assumed that the size of G-rich tracts directly correlates with the formation of secondary structures and polymerase slippage during replication (Mornet et al, 1996 ; Freudenreich et al, 1997 ; Weitzmann et al, 1997 ; Hirst and White, 1998 ).…”
Section: The Fragile X Syndrome — Of Menmentioning
confidence: 99%
“…() showed that the degree of somatic mosaicism is low in an atypical DM1/Charcot Dutch family compared with the expected somatic mosaicism for the corresponding age of sampling and progenitor allele length (Higham & Monckton, ). Different studies have shown that formation of secondary DNA structures, nucleosome positioning, methylation status and transcription level can be affected by the AGG, CAT, GGA, and CCG interruptions described in SCA1, FXS, FRDA, and DM1 (Jarem, Huckaby, & Delaney, ; Mulvihill, Nichol Edamura, Hagerman, Pearson, & Wang, ; Pearson et al., ; Sakamoto et al., ; Santoro et al., ; Volle & Delaney, ). However, the role of interruptions in the mechanisms of TNR stabilization/contraction remains elusive, especially for DM1.…”
Section: Introductionmentioning
confidence: 99%
“…Simplified pathways of the hypothesis are shown in Figure 3 . In addition, perhaps the 6A pattern enhances the stability of CGG repeat tracts [ 22 , 23 ]. Thus, chromosomes with 36 CGG repeats linked to the 6A pattern have become the third most common allele in only Asian populations.…”
Section: Discussionmentioning
confidence: 99%